Disciplining Christians correction and community in Augustine's letters - Ebbeler, Jennifer V. (Oxford studies in late antiquity, 2012)
Disciplining Christians reconsiders several of Augustine's most well-known letter exchanges with close attention to conventional epistolary norms & practices, in an effort to identify & analyze Augustine's adaptation of the traditionally friendly letter exchange to the correction of perceived error in the Christian community